Intra and inter-annual variation in the diet of Magellanic penguin (Spheniscus magellanicus) at Martillo Island, Beagle Channel - Scioscia, Gabriela; Raya Rey, Andrea Nélida; Saenz Samaniego, Ricardo Andres; Florentin, Olga Viviana; Schiavini, Adrian Carlos Miguel (Polar Biology)
Knowledge of seabirds’ diet at each breeding site and its temporal variation is key to understanding and evaluating how changes in marine resources affect each seabird population. In this study, we determined the diet of Magellanic penguins (MP, Spheniscus magellanicus) at Martillo Island, accounting for sex, breeding stage and year. We analyzed a total of 144 stomach contents during three consecutive breeding seasons (2006–2007, 2007–2008 and 2008–2009) and stages (incubation, early and late chick-rearing). MP fed mainly on fuegian sprat (Sprattus fuegensis), which represented 75 % of the biomass consumed by birds during the entire study. The next important prey was squat lobster (Munida gregaria), followed by Patagonian squid (Loligo gahi). Both sexes consumed similar prey items. We observed variation in diet relative composition among breeding years and stages. Fuegian sprat consumption decreased throughout the years whereas squat lobster increased. Penguins consumed a higher proportion of squat lobster and Patagonian squid during the incubation stage than in the chick-rearing stages, whereas fuegian sprat was almost the only prey item consumed during the late chick-rearing stage. MPs show certain flexibility in the use of resources probably as a response to changes in prey populations. Variability in the diet among different reproductive stages could be related to changes in the distribution and abundance of their main prey near the colony during the breeding season together with changes in the energy requirements of seabirds. Fil: Scioscia, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Saenz Samaniego, Ricardo Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Florentin, Olga Viviana. Consejo ...